The impact of artificial intelligence on financial auditing: the case of Algeria - Benachour, Amira; Kaddai, Ramzi; Abdelmalek, Hanane; Bochelgoum, Fella; Tarhlissia, Lamine (Management and Entrepreneurship: Trends of Development, 2025)
This study explores the impact of Artificial Intelligence (AI) on financial auditing in the Algerian context, highlighting its adoption, challenges, and opportunities. To this end, a survey was conducted using a questionnaire distributed to Algerian chartered accountants, statutory auditors, financial auditors, as well as other relevant stakeholders such as former audit firm directors and professionals involved in financial verification and auditing processes in Algeria. This population represents a diverse and representative sample of financial audit professionals, whose perspectives and experiences are essential for assessing the impact of AI on their practices and profession.The study’s findings reveal that AI is transforming auditing practices by improving accuracy, speed, and the detection of anomalies in financial statements. However, its integration raises ethical concerns, particularly regarding algorithm transparency and professional responsibility in interpreting results. Furthermore, auditors using AI tools must be trained not only in traditional auditing, but also in information technology and data analysis. A solid understanding of the fundamentals of machine learning, data analytics, and cybersecurity is essential. They must also remain continuously up to date with technological advances in order to use AI tools effectively in their work.Despite these challenges, the opportunities offered by AI are considerable. It enables auditors to go beyond the limits of manual analysis, facilitating more accurate and data-driven decisions. AI algorithms can analyze vast volumes of transactions to detect anomalies that may indicate fraud, such as duplications, unexplained discrepancies, or unusual transaction patterns. This allows for earlier and more accurate detection, thereby reducing the risk of major fraud.The paper concludes by offering policy recommendations to support the integration of AI into auditing in Algeria, emphasizing the need for capacity building, regulatory reform, and investment in digital infrastructure.JEL Classification: M42, G38, C63, O33, K22